2012
DOI: 10.1103/physreve.85.056106
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic spreading in weighted networks: An edge-based mean-field solution

Abstract: Weight distribution greatly impacts the epidemic spreading taking place on top of networks. This paper presents a study of a susceptible-infected-susceptible model on regular random networks with different kinds of weight distributions. Simulation results show that the more homogeneous weight distribution leads to higher epidemic prevalence, which, unfortunately, could not be captured by the traditional mean-field approximation. This paper gives an edge-based mean-field solution for general weight distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…At this point, the weighted SIS model degenerates to the unweighted one, or it is equivalent to the most homogeneous case with all weights are the same. Therefore, the results are in accordance with the known conclusion [31] that in the absence of correlation between structure and weight, the most homogeneous weight distribution leads to the widest epidemic spreading.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At this point, the weighted SIS model degenerates to the unweighted one, or it is equivalent to the most homogeneous case with all weights are the same. Therefore, the results are in accordance with the known conclusion [31] that in the absence of correlation between structure and weight, the most homogeneous weight distribution leads to the widest epidemic spreading.…”
Section: Discussionsupporting
confidence: 90%
“…Yan et al [30] investigated the epidemic spreading in weighted scale-free networks and the simulation results indicated that the more homogeneous weight distribution of the network is, the more quickly epidemic spreads on it. This finding was further demonstrated by an edge-based mean-field solution [31]. Chu et al [32] showed that weight distribution has strong impacts on both epidemic threshold and prevalence.…”
Section: Introductionmentioning
confidence: 83%
“…Scores of researchers have proven that the strong heterogeneity of degree distribution can reduce or even vanish the epidemic threshold under some certain conditions [e.g., on the scale-free networks of degree distribution p(k) ∼ k −γD with degree exponent γ D ≤ 3 in thermodynamic limit] [15,16]. On weighted networks, some researches have shown that the inhomogeneity of weight distribution can also significantly affect the epidemic dynamics, such as the epidemic threshold and epidemic prevalence [17][18][19][20][21][22][23][24]. For instance, Zhou et al suggested that increasing the dispersion of weight distribution can reduce the velocity of epidemic spreading as well as the epidemic prevalence [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al have studied the effect of connection patterns on the outbreak of epidemic. They have found that a heterogeneous network structure accelerates the spread of infectious disease [38,39,40,41]. K. P. Chan et al have investigated the effect of aging and links removal on epidemic spread in scalefree networks.…”
Section: Introductionmentioning
confidence: 99%